2006
DOI: 10.1002/pmic.200500368
|View full text |Cite
|
Sign up to set email alerts
|

The tegument surface membranes of the human blood parasite Schistosoma mansoni: A proteomic analysis after differential extraction

Abstract: The blood fluke Schistosoma mansoni can live for years in the hepatic portal system of its human host and so must possess very effective mechanisms of immune evasion. The key to understanding how these operate lies in defining the molecular organisation of the exposed parasite surface. The adult worm is covered by a syncytial tegument, bounded externally by a plasma membrane and overlain by a laminate secretion, the membranocalyx. In order to determine the protein composition of this surface, the membranes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
211
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 59 publications
16
211
1
2
Order By: Relevance
“…At the worm surface, the syncytial tegument is connected by cytoplasmic processes to underlying cell bodies which contain the nucleus and molecular machinery necessary for protein synthesis and export. Although Sm29 has no homology to molecules outside of the genus Schistosoma, we can infer that the product is tegument specific, which is an added bonus for our independent proteomic analyses of tegument membrane composition (Braschi et al 2005. Together, these observations imply a role for Sm29 at the tegument surface, possibly in immune evasion.…”
Section: Discussionmentioning
confidence: 91%
“…At the worm surface, the syncytial tegument is connected by cytoplasmic processes to underlying cell bodies which contain the nucleus and molecular machinery necessary for protein synthesis and export. Although Sm29 has no homology to molecules outside of the genus Schistosoma, we can infer that the product is tegument specific, which is an added bonus for our independent proteomic analyses of tegument membrane composition (Braschi et al 2005. Together, these observations imply a role for Sm29 at the tegument surface, possibly in immune evasion.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, several proteomics studies have used EST assemblies, or gene prediction data based on the genome, for peptide searches [29][30][31][32] or have used full-length clones of schistosome genes that resulted from further transcriptome sequencing [33]. Using these resources, several strategies have been employed to search for potential novel vaccines and drug targets, as we will describe in detail in the next sections and is summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…First, the targets are only one of probably hundreds of different antigens that are immunogenic during schistosome infection. Secondly, they derive from proteins that are not particularly abundant in the parasites based on proteomic surveys (van Balkom et al, 2005;Braschi et al, 2006). Thirdly, the epitopes derive from a relatively small extracellular loop domain (~10kD) contained within these apical membrane proteins, which are often more difficult than cytosolic or secreted proteins to study as antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Two schistosome tetraspanin proteins, Sm23 and SmTsp2, were selected to validate the utility of the rat scFv library. These proteins were chosen because they are known to be immunogenic in schistosome infected animals (Wright et al, 1990;Tran et al, 2006) and because they are among the very few integral membrane antigens shown to be present within the host-interactive worm surface tegumental membrane (Braschi et al, 2006;Tran et al, 2006) . Four weeks after S. mansoni infection, rats have a moderate titer of serum antibodies against both Sm23 and SmTsp2 ( Fig.…”
Section: Validation Of the Librarymentioning
confidence: 99%